Benchmarking virus concentration methods for quantification of SARS-CoV-2 in raw wastewater (2020)
astewater-based epidemiology offers a cost-effective alternative to testing large populations for SARS-CoV-2 virus, and may potentially be used as an early warning system for SARS-CoV-2 pandemic spread. However, optimal viruses are highly diluted in wastewater, and a validated method to be concentrated for further processing and suitable reference viruses are the main needs to be established for reliable SARS-CoV-2 municipal wastewater detection. For this purpose, we collected wastewater from two European cities during the Covid-19 pandemic and evaluated the sensitivity of RT-qPCR detection of viral RNA after four concentration methods (two variants of ultrafiltration-based method and two adsorption and extraction-based methods). Further, we evaluated one external (Bovine corona virus) and one internal (pepper mild mottle virus) reference virus. We found a consistently higher recovery of spiked virus using the modified ultrafiltration-based method. This method also had a significantly higher efficiency (p-value <0.01) for wastewater SARS-CoV-2 detection. The ultracentrifugation method was the only method that detected SARS-CoV-2 in the wastewater of both cities. The pepper mild mottle virus was found to function as a potentially suitable internal reference standard.